2020
DOI: 10.3390/molecules25184322
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Inflammatory Cytokine Release from IL-1β and LPS-Stimulated PBMC Orchestrated by ST2825, a MyD88 Dimerisation Inhibitor

Abstract: The inflammatory process implicates homeostasis disruption and increased production of inflammatory mediators. Myeloid differentiation primary response 88 (MyD88) is an essential protein recruited after lipopolysaccharide (LPS) and interleukin (IL)-1β stimulation, a process that converges in nuclear factor kappa B (NF-κB) activation, as well as a transcription of several genes of both pro- and anti-inflammatory cytokines. The inhibition of MyD88 has shown efficacy by decrease inflammatory response, and has dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, we also investigated whether limonin alleviates osteoarthritis in mice through any other pathways. Previous studies have reported that IL-1 β can activate Myd88 [ 39 , 40 ]. Myd88 is the most critical effector molecule in the signal transduction of TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also investigated whether limonin alleviates osteoarthritis in mice through any other pathways. Previous studies have reported that IL-1 β can activate Myd88 [ 39 , 40 ]. Myd88 is the most critical effector molecule in the signal transduction of TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, these bind with the BB-loop of the TIR domain on MyD88, hence, thwarting MyD88 homo-dimerization. This is associated with the abrogation of the signaling involving MyD88, TIRAP and TLR4, and therefore, myddosome formation [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Aryl hydrocarbon receptor, known as Th17 cell differentiation promoter ( Nakahama et al, 2011 ; Talbot et al, 2018 ), and TREM1 signalling involved in systemic and local inflammatory process activation ( Kuai et al, 2009 ; Peng et al, 2019 ; Inanc et al, 2021 ), were also processes identified to be associated with the DMARDs-naïve RA PBMC. Based on our previous findings of the role of ST2825 in downregulating the release of proinflammatory cytokines in PBMC from healthy subjects ( Ramírez-Pérez et al, 2020 ); we tested whether this chemical compound could modulate gene expression signatures and canonical pathways on PBMC from RA patients. Our findings indicate that ST2825 downregulates an enormous number of genes that are increased in RA patients compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The MyD88 inhibitor ST2825 was added to the corresponding well 30 min before stimulation with LPS or rhIL-1β. A treatment concentration of 30 μM ST2825 was chosen based on our previous study in healthy PBMC ( Ramírez-Pérez et al, 2020 ). Experiments were done in duplicates, and PBMC were incubated for 24 h at 37°C in a humidified 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation